Managing innovation and sustaining excellence Proceedings of the International Management Accounting Conference 6, 26 - 27 March 2012, Equatorial Hotel, Bangi, Selangor - International Management Accounting Conference 2012 : Bangi, Selangor); Rozita Amiruddin; Aini Aman.; Azlina Ahmad; Harlina Mohd Onn.; Zakiah Muhammadon Muhammad; Universiti Kebangsaan Malaysia. Fakulti Ekonomi dan Pengurusan (Bangi : Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2012)
Contains 30 papers presented at Proceedings of the International Management Accounting Conference 6. This papers divided into 8 sessions.
System requirement: Adobe Acrobat Reader.
Keywords: Managerial accounting -- Congresses; Accounting -- Malaysia -- Congresses